Ethos and Pedagogical Communication: Suggestions for Enhancing Credibility in the Classroom - William A. Haskins (Current Issues in Education, 2015)
Whether at the conscious or unconscious level, a student's perception of the teacher's ethos, or speaker's character, has an important impact on how he or she will react to the teacher and how effective the teacher will be in the classroom. Erosion of a teacher's ethos can quickly spell disaster in the classroom.